Fortacin™ Spray for the Treatment of Premature Ejaculation - Porst, Hartmut (Urologia, 2017)
Premature ejaculation (PE) is a common complaint of male sexual dysfunction affecting men and their partners and consequently causing significant personal and interpersonal distress. Increased sensitivity of the glans penis and abnormalities of the afferent-efferent reflex pathway within the ejaculatory process are involved in the occurrence of PE. Drugs that either selectively reduce penile sensitization or modify the afferent-efferent reflex are well established therapeutic options for PE. Fortacin™ is the first topical treatment to be officially approved for the treatment of primary PE in adult men, and is mentioned as an experimental aerosol (as TEMPE) in the current European Association of Urology guidelines. It was approved for use in the European Union and launched in the United Kingdom in November 2016. Fortacin™ is a eutectic-like mixture of lidocaine 150 mg/mL and prilocaine 50 mg/mL that meets the requirements of an ideal treatment for PE because it is fast acting (within 5 minutes), has durable effects, can be easily used “on-demand”, and shows minimal side-effects. The metered-dose spray delivery system allows the desensitizing agents to be deposited in a dose-controlled, concentrated film onto the glans penis consequently reducing its sensitivity. This is translated into a delaying of the ejaculatory latency time without adversely affecting the sensation of ejaculation and orgasmic pleasure. The efficacy and safety of Fortacin™ have been proven by means of increased ejaculatory latency, control, and sexual satisfaction in large scale studies demonstrating the significant benefits for both patients and their partners.